Phyllis Schlafly and Grassroots Conservatism : A Woman's Crusade - Critchlow, Donald T., 1948- (Book collections on Project MUSE., 2008)
Based on access to Schlafly's papers and sixty other archival collections, offers a look at the private life and public convictions of the arch-conservative and determined opponent of the Equal Rights Amendment, gay rights, and reproductive freedom.